1993
DOI: 10.1128/jvi.67.11.6453-6462.1993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical bases for activation of the transforming potential of the proto-oncogene c-ros

Abstract: The transforming gene of avian sarcoma virus UR2, v-ros, encodes a receptor-like protein tyrosine kinase and differs from its proto-oncogene, c-ros, in its 5' truncation and fusion to viral gag, a three-amino-acid (aa) insertion in the transmembrane (TM) domain, and changes in the carboxyl region. To explore the basis for activation of the c-ros transforming potential, various c-ros retroviral vectors containing those changes were constructed and studied for their biological and biochemical properties. Ufcros … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 44 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Such mutations were found on c‐erbB‐2/neu 9,10. Mutation of the transmembrane domain was also found in other viral oncogenes such as v‐ROS, which obtains a broad substrate specificity 11…”
Section: Receptor Tyrosine Kinases In Human Cancermentioning
confidence: 82%
See 1 more Smart Citation
“…Such mutations were found on c‐erbB‐2/neu 9,10. Mutation of the transmembrane domain was also found in other viral oncogenes such as v‐ROS, which obtains a broad substrate specificity 11…”
Section: Receptor Tyrosine Kinases In Human Cancermentioning
confidence: 82%
“…9,10 Mutation of the transmembrane domain was also found in other viral oncogenes such as v-ROS, which obtains a broad substrate specificity. 11 Alternatively, tyrosine kinases can become oncogenic by mutations that make them active and independent of ligand binding or dimerization. Nonreceptor tyrosine kinases are also activated by mutations that affect their negative regulation, such as the mutation on tyrosine 527 of Src that leads to deregulation of its activation.…”
Section: Receptor Tyrosine Kinases In Human Cancermentioning
confidence: 99%
“…Expression of ROL‐3 in epidermal tissues is consistent with the murine model, demonstrating the potential for a conserved function between these proteins. It has been demonstrated that ROS1 directly binds SH2 domain containing tyrosine phosphatase SHP‐1 (Keilhack et al, ), and has been shown to activate both SHP‐1 and SHP‐2, the mitogen‐activated protein kinase ERK1/2, insulin receptor substrate 1 (IRS‐1), phosphatidylinositol 3‐kinase (PI3K), protein kinase B (AKT) and the STAT3 and VAV3 signaling pathways (Zong et al, ; Xiong et al, ; Zeng et al, ; Charest et al, ). Orthologs of several of these proteins are present in the C. elegans genome, leading to potential future studies to test the conserved nature of these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…DNA Transfections-Transfections were done using the calcium phosphate co-precipitation method (31). Primary CEFs were plated at a density of 1 ϫ 10 6 cells/6-cm dish and incubated for 18 -20 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The medium was then replaced with fresh medium containing 10% calf serum. 50 l of 2.5 M CaCl 2 was added to 450 l of sterile H 2 O containing 10 g each of transforming viral plasmid DNA and SacI-digested UR2AV helper viral DNA (31). This solution was slowly added to 500 l of 2 ϫ Hepes-buffered saline (50 mM Hepes, pH 7.2, 280 mM NaCl, 10 mM KCl, 1.5 mM Na 2 HPO 4 , and 12 mM dextrose) that was being aerated.…”
Section: Methodsmentioning
confidence: 99%